Pengaruh Penghargaan Finansial, Pelatihan Profesional, dan Pengakuan Profesional Terhadap Pemilihan Karir Sebagai Akuntan Publik Bagi Mahasiswa Akuntansi - Hidayat, Alfian Fatkhur; Wahyono, Wahyono (Prosiding University Research Colloquium, 2021)
The career choice of accounting students as public accountants can be influenced by several factors, including financial rewards, professional training, and professional recognition. The purpose of this research is to analyze and obtain empirical evidence about the effect of financial rewards, professional training, and professional recognition on career choices as public accountants. This research is a quantitative descriptive study using primary data in the form of a questionnaire distributed to students majoring in Accounting at the Muhammadiyah University of Surakarta. The results showed that financial rewards and professional training had no effect (statistically insignificant) on career choices as public accountants, while professional recognition had a significant effect (statistically significant) on career choices as public accountants for UMS accounting students.